Narra Ludens: explaining video game narrative engagement through player types and motivations - Şengün, Sercan (İstanbul Bilgi Üniversitesi, 2016)
[Abstract Not Available]
Narra Ludens: video oyun anlatıları ile etkileşimin oyuncu türleri üzerinden açıklanması